Leakage‐Proof Electrolyte Chemistry for a High‐Performance Lithium–Sulfur Battery. Issue 30 (22nd June 2021) - Ju, Jiangwei; Dong, Shanmu; Cui, Yanyan; Zhang, Yanfen; Tang, Ben; Jiang, Feng; Cui, Zili; Zhang, Huanrui; Du, Xiaofan; Lu, Tao; Huang, Lang; Cui, Guanglei; et al.
Abstract: Electrolyte leakage is a severe safety concern in lithium batteries. With highly volatile 1, 2‐dimethoxyethane as solvent, the leakage related hazards are more pronounced in lithium‐sulfur (Li‐S) batteries. To address this concern, a leakage‐proof electrolyte is delicately designed through functionalizing the commercial electrolyte by Li6 PS5 Cl‐grafted poly(ethyl cyanoacrylate), which can interact readily with the aluminum‐plastic packing through hydrogen bond to immobilize the electrolyte. The moisture from ambient can also catalyze a further polymerization of the macromolecules to seal the leaking points and thereby to solve the leakage issue, endowing Li‐S batteries superior safety even in an artificial cut pouch cell. With a bare S loading of 4.9 mg cm −2, the battery can deliver good endurance owing to the suppressed polysulfide shuttle by its polar groups. This work enlightens the design of leakage‐proof electrolyte and makes a milestone for high performance Li‐S batteries. Abstract : The 1, 2‐dimethoxyethane‐based electrolyte is functionalized by Li + ‐conductive macromolecules of Li6 PS5 Cl‐grafted poly(ethyl cyanoacrylate) with strong polar groups, which can interact readily with the aluminum‐plastic packing layer through hydrogen bond to immobilize the electrolyte. And the moisture from ambient environment can catalyze a further polymerization of the macromolecules to seal the leaking points.